2007
DOI: 10.4028/www.scientific.net/msf.546-549.2279
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Green Tapes for LTCC/Cu Multilayer Substrates

Abstract: The green tapes of Al 2 O 3 /glass composite were prepared by tape casting process using poly methyl methacrylate (PMMA) as a binder. The results show that the slurry for tape casting exhibits a typical shear thinning behavior. The best pyrolysis procedure was found in nitrogen atmosphere to a maximum temperature of 600°C. The dielectric constants are between 4.6 and 7.3 depending on the glass content. The dissipation factors are about 0.2 % in the frequency range from 1 KHz to 1 MHz. The green tapes using PMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Commercial tubular BASE membranes are generally produced by isostatic dry bag pressing, although Ionotec also uses electrodeposition and extrusion for the production of certain geometries [17]. By comparison, tape casting is a commercially established method for producing flat ceramic sheets for applications including microelectronic circuits and fuel cells [18][19][20]. Lu et al describe tape casting of Na-β"-Al 2 O 3 , where they found that PMMA binder with a mixed MEK/ethanol solvent system provided much more consistent results than tapes based on PVB in water [16].…”
Section: Tape Casting and Warm Laminationmentioning
confidence: 99%
“…Commercial tubular BASE membranes are generally produced by isostatic dry bag pressing, although Ionotec also uses electrodeposition and extrusion for the production of certain geometries [17]. By comparison, tape casting is a commercially established method for producing flat ceramic sheets for applications including microelectronic circuits and fuel cells [18][19][20]. Lu et al describe tape casting of Na-β"-Al 2 O 3 , where they found that PMMA binder with a mixed MEK/ethanol solvent system provided much more consistent results than tapes based on PVB in water [16].…”
Section: Tape Casting and Warm Laminationmentioning
confidence: 99%